Potensi Tumbuhan Pakan Dan Lokasi Tidur Kukang Kalimantan (Nycticebus menagensis) Di Desa Tenguwe Kabupaten Landak - Indah Winarti, Belianto, Elvi Rusmiyanto Pancaning Wardoyo, (Universitas Tanjungpura, 2017)
Bornean slow loris (Nycticebus menagensis) are endemic to Borneo. Slow loris that live outside conservation area has high potential of disturbance, because lacking of protection. One habitat outside conservation area is Tenguwe Village, Air Besar Subdistrict, Landak Regency. This study aims to obtain information on plants and plant parts used by slow loris as a food source and a sleeping site. The research was conducted in March to April 2016. The methods used were semi-structured interviews and surveys of existence. Interviews were conducted to obtain information on the existence of slow loris, plant food resources and sleeping sites. The respondents interviewed were selected using a snowball sampling technique. The results of the interviews were followed up by conducting survey in the forest. Data were analyzed descriptively. The research obtained 32 species of 17 families of plants potentially as food and 4 species of 4 families of plants potentially as for sleeping sites. The results also show that slow loris at Tenguwe village are hunted for food, pets and sold. The slow loris found were two individuals in two different locations namely Sengabu and Bejawi.